The Book of Mormon's Message on Brotherhood - Sperry, Sidney B. (Journal of Book of Mormon studies, 1995)
The Book of Mormon exhibits the intimate relationship between God and his people. The brother of Jared's experience is a fine example. The driving force of the prophets was moral and religious, rather than economic and political. Social injustice was condemned by Nephi, Jacob, Alma, and Captain Moroni. Although little is said about the status of the family, respect for women and family affection are standard. Workers were well treated and friendship was promoted between Nephites and Lamanites. The Book of Mormon displays a high caliber of personal religion and brother hood.